C-ORGANIC CONTENT IN THE SEAGRASS LEAF ON DIFFERENT KINDS SEAGRASS OF ISLAND PONCAN IN SIBOLGA, NORTH SUMATERA PROVINCE - Yohanna Siagian; Zulkifli '; Efriyeldi ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
This research was conducted from March to May 2017, at Poncan Island. This study aims to determine the content of organic carbon in the leaf seagrass on different species in the waters of Poncan Island, Sibolga, North Sumatera. Tools and materials used in the field are transect rope, thermometer, pH Indicator, secci disk. The tools used in the laboratory are alluminium foil, oven, furnace, analytical scales and materials used in the laboratory is seagrass, sediment and H2O2 samples. This method uses the Survey method. The organic carbon content was analyzed by the method of sampling and the data was processed using the t-test. The results show the dock area and the area affected by the highest C-organic waste waste in the H. unninervis species. In mangrove areas and areas where there is no highest C-organic human activity is found in C. rotundata speciesKeywords : C-Organic Content, Poncan Island